Growth of the Albino rat with special reference to the influence of environment - Murray, G.N. (Pretoria : The Government Printer, 2017)
The articles have been scanned in colour with a HP Scanjet 5590; 300dpi. Adobe Acrobat XI Pro was used to OCR the text and also for the merging and conversion to the final presentation PDF-format.